2021
DOI: 10.3389/fcvm.2021.621389
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of CMR, SPECT, and PET Imaging for the Identification of Coronary Artery Disease: A Meta-Analysis

Abstract: Background: Myocardial perfusion imaging modalities, such as cardiac magnetic resonance (CMR), single-photon emission computed tomography (SPECT), and positron emission tomography (PET), are well-established non-invasive diagnostic methods to detect hemodynamically significant coronary artery disease (CAD). The aim of this meta-analysis is to compare CMR, SPECT, and PET in the diagnosis of CAD and to provide evidence for further research and clinical decision-making.Methods: PubMed, Web of Science, EMBASE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The latest meta-analysis evaluating the diagnostic performance of MPI was conducted by Xu et al ( 42 ). They performed a meta-analysis evaluating the diagnostic performance of cardiac magnetic resonance (CMR), MPI and positron emission tomography (PET) and reported that MPI had a pooled sensitivity of 0.83 and a pooled specificity of 0.77.…”
Section: Discussionmentioning
confidence: 99%
“…The latest meta-analysis evaluating the diagnostic performance of MPI was conducted by Xu et al ( 42 ). They performed a meta-analysis evaluating the diagnostic performance of cardiac magnetic resonance (CMR), MPI and positron emission tomography (PET) and reported that MPI had a pooled sensitivity of 0.83 and a pooled specificity of 0.77.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional SPECT systems use large sodium iodide crystals, photomultiplier tubes, and parallel-hole collimation, with relevant drawbacks such as prolonged imaging times and relatively large radioisotope doses. Furthermore, overall diagnostic accuracy, having invasive functional assessment as reference standard, has been shown to be lower than desirable [14,21,32].…”
Section: Single-photon Emission Computed Tomographymentioning
confidence: 99%
“…Owing to the suboptimal quality of images obtained with 201 TlCl, as well as the high price and di cult availability of this radiotracer, it has been replaced during the last decade by 99m technetium-labeled agents that are taken up by the myocardiocytes by passive transport, including SestaMIBI in the rst place. Essentially, myocardial perfusion single-photon emission computed tomography (SPECT) studies have been undertaken worldwide exclusively with two-detector gamma cameras dedicated to cardiac imaging, which depict abnormalities of myocardial blood supply with a sensitivity and speci city of 80 per cent on average [2]. Dedicated SPECT cameras developed for cardiac studies allowed to improve image quality, increase resolution, enhance image contrast, and reduce picture noise -consequently reducing patient dose compared to general-purpose gamma cameras [3].…”
Section: Introduction and Objectivesmentioning
confidence: 99%